From Collective Enthusiasm to Individual Self-Realization: History of and Experience in the House of Culture, Anadyr’ (Chukotka) - Virginie Vaté; Galina Diatchkova (Reconstructing the House of Culture, 2011)
Anne White has observed that cultural enlightenment, ... as an activity organized by the regime in Soviet-type systems, ... is an area of ideological work. It involves the socialization of adults and children in their spare time through participation in non-professional arts and other cultural activities. ... Its three basic principles are belief in the need to equalize access to culture, belief that such access can change human behaviour, and belief that the party can and must control the nature of the culture which is created and provided. (1990: 1) One might assume that, ater the end of the Soviet